Hydrodynamics (Reynolds number) determine scaling, nucleation and crystal growth kinetics in membrane distillation crystallisation - Jikazana, Aphiwe; Campo Moreno, Pablo; McAdam, Ewan (Elsevier, 2023)
Reynolds number (Re) has been previously related to several scaling mitigation and crystallisation strategies that offer distinct hypotheses for how Re may regulate the kinetics of nucleation and crystal growth in membrane crystallisation. Such ambiguity has arisen from the present inability to discretely characterise induction time in membrane systems. This study therefore introduces techniques for the detection of induction time, with measurements used to develop a modified power-law relation between nucleation rate and supersaturation to establish how Re can be used to adjust nucleation kinetics. Increasing Re enhanced mass and heat transfer processes which raised permeate flux. The interfacial supersaturation set by the increase in flux, also modified the supersaturation rate at induction for crystals formed in the bulk solution, providing the first direct evidence that it is the supersaturation level set within the boundary layer which controls primary nucleation in the bulk solution. Bulk nucleation rate can therefore be adjusted in proportion to Re. While the extent of scaling was also determined by the interfacial supersaturation set by Re, its formation was shown to be more dependent on the interfacial diffusion coefficient which regulates solute backtransport and the activation energy for nucleation. Through this work we suggest that the nucleation mechanisms underlying scale formation and bulk crystallisation are distinct. The regulation of nucleation rate in the bulk solution by Re is described analytically through classical nucleation theory, while scaling can be mitigated through operation below a critical threshold supersaturation value that determines the rate and type of scaling that prevails. These seemingly distinct strategies can be combined through modifications to T and dT with Re to suppress scaling and offer refined control over the kinetics of nucleation and crystal growth.
Keywords: Mixing; Primary nucleation; Evaporative; Brine; Zero liquid discharge; NaCl